ANALISIS PEMASARAN DAN TRANSMISI HARGA PADA PETANI BAHAN OLAHAN KARET (BOKAR) DI DESA SEI TONANG KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Ermi Tety '; Evy Maharani '; Fitria Ningsih ' (PEKBIS, 2015)
This research aim is to know and analyze: 1. the channel, margin of bokar marketingand bokar marketing efficiency and the price that farmer received. 2. The correlationbetween the price of bokar from factory and the price of bokar in farmer level. 3. Theinfluence of bokar price changing of factory to farmer level at sei tonang village ofKampar utara district of Kampar regency. The research method is used of surveymethod. The sampling method is purposive sampling of 38 farmer that have plantationage between 20-25 years. And the second sampling of merchant is using snowballsampling method that come to marketing channel. The research results shows that inSei Tonang village of Kampar Utara district of Kampar regency have one rubbermarketing channel ( homogeneity). That is farmer to collector merchant to factory. Thelowest price in farmer level is Rp. 7.966,67 /kg, and the highest price level is Rp.11.800,00/kg. Then the lowest price of factory is Rp. 11.733,33/kg, and the highestprice level of factory is Rp. 16.516,67/kg. The average price level of the farmer levelon year 2012 is Rp.9.720,97 and the average price level on factory is Rp.13.872,78.The margin level of marketing channel between the price in farmer level and factoryis Rp. 4.151,81 and farmer received 73.44% and marketing eficiency is 3.07%. thecorrelation value between the price in farmer level and factory level is 0,826 %. Thevalue of the elasticity of price transmission between the price received from farmersand the price of bokar by factory was 0,723.Keywords : Marketing channels, marketing margins, price transmission elasticity